Mechanism of action of PD‐1 receptor/ligand targeted cancer immunotherapy. Issue 8 (21st June 2021) - Borst, Jannie; Busselaar, Julia; Bosma, Douwe M. T.; Ossendorp, Ferry
Abstract: Immunotherapy targeting the Programmed Death (PD‐1) receptor/ligand (L) "checkpoint" rapidly gains ground in the treatment of many cancer types. To increase treatment scope and efficacy, predictive biomarkers and rational selection of co‐treatments are required. To meet these demands, we must understand PD‐1 function in detail. We here outline recent insights into the regulation of the CD8 + T cell response by PD‐1. The prevailing view has been that blockade of PD‐1/ligand (L) interaction "reinvigorates" cytotoxic T lymphocytes (CTL) that were rendered dysfunctional in the tumor microenvironment (TME). However, this review stresses that tumors continuously communicate with adjacent draining lymph nodes (LNs) and that the PD‐1 checkpoint also operates during T cell priming. We clarify the role of the PD‐(L)1 system at the T cell/DC interface, where it regulates T cell receptor (TCR) signaling and CD28 costimulation and thus controls activation of tumor‐specific T cells. We also highlight the importance of CD4 + T cell help during priming, which allows DCs to provide other costimulatory and cytokine signals required for optimal CTL differentiation and likely avoidance of a dysfunctional state. Therefore, we pose that PD‐(L)1 blockade should exploit LN function and be combined with "help" signals to optimize CTL efficacy. Abstract : Novel insights into exhaustion and PD‐1 signaling during T‐cell priming have challenged the classical view on the mechanisms underlying PD‐(L)1‐targeted therapy. This review integrates the latest findings on anti‐PD‐(L)1 responsive T cells, such as differentiation state, location, and molecular interactions, into a comprehensive model of PD‐(L)1 blockade effects in cancer.